GAMBARAN PENGETAHUAN DAN SIKAP PEKERJA PENAMBANG EMAS TANPA IZIN (PETI) MENGENAI PARAMETER PENCEMARAN AIR SUNGAI BATANG HARI DI NAGARI PINTIN KAYU KECAMATAN KOTO PARIK GADANG DI ATEH KABUPATEN SOLOK SELATAN - Yeni Herlina; Riska Ayunda Putri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
Officially, community-managed gold mining activities are not permitted by the government, either at the provincial or district levels. One of the most troubling problems for the community around the Unlicensed Gold Mining (PETI) location is the use of toxic hazardous materials (B3), namely; mercury (Hg). The purpose of this study was to determine the description of knowledge and attitudes of unlicensed gold mining workers (PETI) regarding water pollution in the Batang Hari River in Nagari Pintin Kayu, Koto Parik Gadang District, Ateh, South Solok Regency. The design of this research is descriptive. This research was conducted in Nagari Pintin Kayu, Koto Parik Gadang Diateh District, South Solok Regency, which was conducted in October 2020, the population in this study were all Unlicensed Gold Mining (PETI) workers in Nagari Pintin Kayu, totaling 48 people. All populations were used as research subjects with total sampling technique. Questionnaire measuring instruments and univariate data analysis were presented in the form of frequency distribution tables and percentages. The results of the study were more than half of the 29 people (60.4%) had low knowledge about water pollution of the Batang Hari River and more than half of the 26 people (54.2%) had a negative attitude about water pollution of the Batang Hari River. Nagari Pintin Kayu, Koto Parik Gadang District, Ateh, South Solok Regency, to raise awareness about river water pollution due to illegal gold mining.